Advances in the mineralogical characterization of soils from the Chancay River, Lambayeque, by X-ray difraction and Mössbauer spectroscopy - Trujillo Quinde, Alejandro L. (2011)
This paper reports the preliminary results of the mineralogical characterization of soils from the Chancay River Valley, Lambayeque, by X ray diffractometry (XRD) and transmission Mössbauer spectroscopy (TMS). The studied soil sample, SI53, belongs to one of the two horizons of a selected soil profile from the area of Sialupe, located in the Chancay River Valley. The XRD allowed the identification of crystalline mineralogical phases in the such as found sample, at a depth of 30 cm, such as quartz, montmorillonite, clinochlore, amphibole and albite; these same minerals, except amphibole, appear also in its corresponding clay fraction. The TMS allowed the identification , in the such as found sample, of a sextet assigned to hematite and a central doublet that can be assigned to an iron oxide in the super paramagnetic state or to kaolinite; the other doublets are assigned to montmorillonite, muscovite and epidote. All of these phases, with the exception of epidote, are also identified in the clay fraction by TMS.